Mechanical circulatory support devices and treatment strategies for right heart failure - Kuroda, Taiyo; Miyagi, Chihiro; Fukamachi, Kiyotaka; Karimov, Jamshid H. (Frontiers in Cardiovascular Medicine, 2022)
The importance of right heart failure (RHF) treatment is magnified over the years due to the increased risk of mortality. Additionally, the multifactorial origin and pathophysiological mechanisms of RHF render this clinical condition and the choices for appropriate therapeutic target strategies remain to be complex. The recent change in the United Network for Organ Sharing (UNOS) allocation criteria of heart transplant may have impacted for the number of left ventricular assist devices (LVADs), but LVADs still have been widely used to treat advanced heart failure, and 4.1 to 7.4% of LVAD patients require a right ventricular assist device (RVAD). In addition, patients admitted with primary left ventricular failure often need right ventricular support. Thus, there is unmet need for temporary or long-term support RVAD implantation exists. In RHF treatment with mechanical circulatory support (MCS) devices, the timing of the intervention and prediction of duration of the support play a major role in successful treatment and outcomes. In this review, we attempt to describe the prevalence and pathophysiological mechanisms of RHF origin, and provide an overview of existing treatment options, strategy and device choices for MCS treatment for RHF.